Polisaccharides influence on the interaction between tannin acid and haze active proteins in beer - Lataza Rovaletti, Mercedes (2014)
Colloidal instability in beer is mainly caused by interactions between proteins and polyphenols. These two combine producing a visible haze that reduces the physical shelf life of beer. The haze active proteins (HAPs) react with tannic acid (TA); therefore, this reaction provides a way to determine HAP concentrations in beer. Beers also contain a number of constituents that may influence the protein-polyphenol haze formation. We used a response surface methodology to predict the influence of total polysaccharides (TPS) and proteins on beer haze. Experiments were carried out using the Central Composite Design (CCD) methodology. Samples of beer were prepared with variable concentrations of TPS and proteins. TPS concentrations ranged between 1.34 and 2.23gL-1 and proteins concentrations between 0.11 and 0.18gL-1. Results show that the increase in turbidity in response to TPS addition was similar to that in response to protein addition. Our regression analyses indicate a significant dependency and correlation between the observed values and the predicted response values (R2=97.87% and R2[adj]=95.75%). Furthermore, these values indicate that our experimental model can explain 95.75% of the total variation. Therefore, using TA as an indicator of the interaction of TPS with proteins, as commonly done, can lead to considerable errors, since the polysaccharides also react with TA, and this reaction actually causes a considerable increase in turbidity.